Literasi Digital Pembelajaran Guru SMKN di Kabupaten Wajo - Muhammad Agus; Ansar; Sumarlin Mus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study describes the description of digital literacy of SMKN teacher learning in Wajo Regency. This study uses a quantitative approach with a descriptive research type to explain the condition of the description of digital literacy of teacher learning. The population in this study was 269 teachers with sampling using simple random sampling so that a sample of 161 was obtained. The data collection techniques used were surveys and documentation. The analysis technique used was descriptive statistical analysis. In this study, digital literacy of teacher learning consists of finding digital content, creating digital content, using digital content and communicating digital content. The results of the study showed that digital literacy of teacher learning was in the high category, this can be seen from several dimensions that were measured. First, the teacher's ability to find digital content is in the very high category which shows the teacher's excellent skills in finding and accessing relevant digital information. Second, the teacher's ability to create digital content is in the high category which means that the teacher is able to create digital materials quite creatively and effectively. Furthermore, the teacher's ability to use digital content is also in the high category which shows that the teacher actively uses digital materials to support the learning process. Finally, the teacher's ability to communicate digital content is also in the high category, meaning that the teacher is able to convey digital material to students clearly and well. Thus, teachers have good digital literacy skills to support the learning process. They are not only able to find and use various digital content, but also can create and communicate learning materials effectively.